2017
DOI: 10.1115/1.4036093
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Reduction of Detailed Chemical Reaction Mechanisms for Engine Applications

Abstract: In this work, we apply a sequence of concepts for mechanism reduction on one reaction mechanism including novel quality control. We introduce a moment-based accuracy rating method for species profiles. The concept is used for a necessity-based mechanism reduction utilizing 0D reactors. Thereafter a stochastic reactor model for internal combustion engines is applied to control the quality of the reduced reaction mechanism during the expansion phase of the engine. This phase is sensitive on engine out emissions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…A recently developed detailed ETRF reaction scheme; 32 A reduction methodology targeted to auto-ignition and laminar flame speed prediction; 37 A surrogate formulation for gasoline; 10,44 A combination of the level-set method to track the turbulent flame development and well-stirred reactors in the burned and unburned gases; 45 A post-processing strategy to evaluate knock occurrence and severity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently developed detailed ETRF reaction scheme; 32 A reduction methodology targeted to auto-ignition and laminar flame speed prediction; 37 A surrogate formulation for gasoline; 10,44 A combination of the level-set method to track the turbulent flame development and well-stirred reactors in the burned and unburned gases; 45 A post-processing strategy to evaluate knock occurrence and severity.…”
Section: Resultsmentioning
confidence: 99%
“…Since auto-ignition and the flame propagation are physically independent and modeled as separate processes, it was decided to split up the reduction process to these two targets (see Figure 1). For both skeletal schemes, a reduction procedure using the chemistry-guided reduction concept introduced by Zeuch et al, 38 which was further developed with special emphasis on engine simulation by Seidel et al, 37 was applied. The early oxidation pathways of the fuel species are formulated independently from each other.…”
Section: Chemical Model and Surrogate Formulationmentioning
confidence: 99%
“…More details on the lumping methodology can be found in Ref. . Thermodynamic and molecular properties are stored externally as they are not generated by the software.…”
Section: Mechanism Generatormentioning
confidence: 99%
“…This reaction scheme was also used in the past as base chemistry for the development of a rule‐based n ‐heptane chemistry by Refs. and . The reaction scheme is composed of 201 species and 1231 reactions.…”
Section: Selected Base Chemistriesmentioning
confidence: 99%
“…The QD-SRM is already applied to investigate the effect of different octane number fuels on autoignition in the end gas as shown by Netzer et al 20 The detailed chemistry for multi-component fuels used in that work as well as in the presented work is based on the methodology of reaction mechanism development and reduction introduced by Seidel and colleagues. 21,22 The sensitivity of detailed chemistry for water injection is investigated in detail by Netzer et al 23 The authors separated the thermodynamic and chemical effects of water injection and showed how laminar flame speed, vaporization, heat capacity, chemical equilibrium, third-body reactions and ignition delay are influenced by water injection. To reduce the computational cost of the QD-SRM simulations, Lehtiniemi et al 24,25 and Matrisciano et al 26,27 proposed a reaction-progress-variable-based tabulation strategy.…”
Section: Introductionmentioning
confidence: 99%